A Comparative Analysis of Museum Accessibility in High-Density Asian Cities: Case Studies from Seoul and Tokyo - Xiaolong Zhao; Jinju Lee; Kwanseon Hong (Buildings, 2023)
We investigated the relationship between urban accessibility of museums in the urban spaces of Tokyo and Seoul within limited travel distances. Similarities and differences were identified in the museum accessibility between the two cities. The urban accessibility of museums was set as the dependent variable, calculated via space syntax. For the spatial accessibility of museums, five walking ranges (1000–2000 m) were set as independent variables, with a distance of 250 m as the basic unit. Data normality and independence of the derived data were checked, and polynomial curve fitting was performed to interpret the accessibility of museums in each city. A comparative analysis was conducted on museum accessibility. The results show areas with a high concentration of museums in Tokyo and Seoul partially deviated from the center of the urban hierarchy. The urban and spatial accessibilities of museums in both cities quantitatively correlated with limited travel distances. Museum visitors in Tokyo were more likely to have relatively free-flowing routes in the city. The museums in Seoul had a lower overall accessibility than those in Tokyo, and travel patterns and routes to these museums were likely to be restricted when located in urban areas and consequently resembled a forced movement pattern.